NIDHAL GUESSOUM’S METHOD OF SCIENTIFIC INTERPRETATION: AN ANALYTICAL STUDY ON AL-AYAH AL-KAUNIYYAH AND ITS RELEVANCE TO THE CONTEMPORARY URBAN MUSLIM SOCIETY - Muhammad Faqih Nidzom; Herlina Yunita Amroin; Utama Cahya Ramadhan, Mahendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
The scientific interpretation of the Qur’an seeks to reconcile revelation with modern science through a rational and contextual approach. Within this field, Nidhal Guessoum, an astrophysicist and philosopher, emerges as a central figure who challenges the iʿjāz ʿilmi paradigm and literalist readings by proposing a multi-layered hermeneutic grounded in theology, language, and ethics. This study addresses the ongoing academic debate between iʿjāz ʿilmi advocates and critical contextualists, identifying the lack of systematic criteria for evaluating scientific interpretation as its primary research gap. The novelty of this research lies in operationalizing Guessoum’s method into a structured analytical framework applicable to contemporary studies. using a qualitative library-based method, the analysis employs close reading and thematic coding across theological, linguistic, and ethical dimensions, followed by a comparative appraisal to trace convergence and divergence between the two frameworks. The findings reveal, first, that Guessoum’s model balances scientific rationality with theological integrity through contextual interpretation; second, it redefines tafsīr ʿilmi as an ethical engagement rather than empirical validation; and third, it provides an interpretive model adaptable to urban Muslim contexts navigating faith and modernity. However, Guessoum’s method offers a critical yet constructive bridge between revelation and scientific inquiry. It contributes theoretically by refining evaluative tools for Qur’anic science discourse and practically by providing implications for educators and urban Muslim institutions to integrate scientific literacy with faith-based education.